Maintaining Clean Environment Inside the Classroom Affecting the Safety and Security of the Grade 12 ABM Students (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This study is about promoting the safety and security of the students by maintaining a clean environment. Students want a pleasant and safe classroom to enjoy studying. Thus, they must learn how to maintain a clean environment. The researchers chose this topic because we always observe the dirt inside the classroom. Many of the students do not care about the trash, especially when they are doing other things. Sometimes, they will wait for the command before cleaning. The researchers made guidelines that will educate the students on how to be safe and be clean inside their classroom. The study can lessen the dirt inside the classrooms. This study used a descriptive research design because the problem is based on researchers’ observations. We used a survey because it isthe most reliable method to obtain real information and opinions about promoting the safety and security of the students by maintaining a clean environment. The respondents of the study were 50 selected Grade 12 Accountancy, Business, and Management students in Bestlink College of the Philippines in S.Y. 2019–2020. The researchers used a nonprobability technique because the researchers do not seek the profile of the respondents and the ease of information gathering using this method. The respondents agreed that maintaining a clean environment can positively affect the classroom ambiance and the safety and security of the students. Moreover, the assessment in terms of accomplishes cleaning tasks showed that they also agreed that the cleaning checklist is extremely effective in maintaining cleanliness. Lastly, the respondents also agreed that the cleaning checklist is extremely effective in maintaining a clean environment inside the classroom through the accomplished cleaning schedule. Based on the results of the study, the students became diligent in cleaning the classroom and monitored the cleanliness by having a checklist. Observing the cleaning schedule was also necessary. The researchers recommended always observe the cleanliness inside the classroom. The students need to be responsible for waste disposal. Cleaning materials should be provided to make the students practice cleaning their rooms.
Keywords: maintaining, clean environment, safety and security